Indoor air quality assessment in dwellings with different ventilation strategies in Nunavik and impacts on bacterial and fungal microbiota. (28th May 2021) - Degois, Jodelle; Veillette, Marc; Poulin, Patrick; Lévesque, Benoit; Aubin, Daniel; Ouazia, Boualem; Brisson, Mario; Maltais, François; Duchaine, Caroline
Abstract: Indoor air quality is a major issue for public health, particularly in northern communities. In this extreme environment, adequate ventilation is crucial to provide a healthier indoor environment, especially in airtight dwellings. The main objective of the study is to assess the impact of ventilation systems and their optimization on microbial communities in bioaerosols and dust in 54 dwellings in Nunavik. Dwellings with three ventilation strategies (without mechanical ventilators, with heat recovery ventilators, and with energy recovery ventilators) were investigated before and after optimization of the ventilation systems. Indoor environmental conditions (temperature, relative humidity) and microbiological parameters (total bacteria, Aspergillus / Penicillium, endotoxin, and microbial biodiversity) were measured. Dust samples were collected in closed face cassettes with a polycarbonate filter using a micro‐vacuum while a volume of 20 m 3 of bioaerosols were collected on filters using a SASS3100 (airflow of 300 L/min). In bioaerosols, the median number of copies was 4.01 × 10 3 copies/m 3 of air for total bacteria and 1.45 × 10 1 copies/m 3 for Aspergillus / Penicillium . Median concentrations were 5.13 × 10 4 copies/mg of dust, 5.07 × 10 1 copies/mg, 9.98 EU/mg for total bacteria, Aspergillus / Penicillium and endotoxin concentrations, respectively. The main microorganisms were associated with human occupancy such as skin‐related bacteria or yeasts, regardless of the type of ventilation.